Multicompartment Model of an Ethylene-Vinyl Acetate Autoclave Reactor: A Combined Computational Fluid Dynamics and Polymerization Kinetics Model - Lee, Yongkyu; Jeon, Kyeongwoo; Cho, Jiyeong; Na, Jonggeol; Park, Jongmin; Jung, Ikhwan; Park, Jehun; Park, Myung June; Lee, Won Bo (Industrial and Engineering Chemistry Research, 2019)
In this paper, we present a multicompartment model of an ethylene-vinyl acetate autoclave reactor including the mixing effects of the stirring device analyzed using computational fluid dynamics; the model is simplified by cell aggregation, and the polymerization kinetics is modeled with the method of moments. The proposed model has been verified through comparison of the predicted product properties and locally distributed temperatures with those from an industrial plant. The proposed model, which is capable of simulating a complex system with low computational load, can be applied to maintain consistent product quality, prevent undesired thermal runaway, and optimize the conversion and production rates.
Keywords: Autoclave reactors; Ethylene vinyl acetates; Low computational loads; Multi-compartment models; Polymerization kinetics; Product property; Production rates; Stirring devices